Desarrollo de la coordinación mediante juegos recreativos en estudiantes del cuarto año “B” de la Unidad Educativa Padre Julián Lorente, Loja 2023 – 2024. - Villafuerte Encalada, Denis Rene (2024)
The aim of this curricular integration work is to develop motor coordination through a pedagogical proposal of recreational games in the students of the fourth year, parallel "B" of the Padre Julián Lorente Educative Unit of Loja Ecuador. In addition, a mixed approach was used, with an experimental and correlational design, with the support of inductive, deductive and descriptive statistical methods. A diagnostic instrument such as the 3JS test was applied to a sample of 16 students from the fourth year, parallel “B” corresponding to the elementary sub-level. According to the results obtained once the diagnostic test was applied, it is evident that the majority of students were placed in categories 1 and 2, which correspond to immature development, and few students obtained 3 points in the seven tests performed. These results are negative because they demonstrate a low level of coordination. Based on these results, a pedagogical proposal based on recreational games for the development of coordination was designed and applied, which was completed in 11 weeks, 3 classes per week, thus adding 33 sessions of recreational work with activities related to the block of recreational practices: games and playing physical education. Next, the 3JS post-test was applied, where it was evident that the majority of students had increased between 1 and 2 points in each of the seven tests, which demonstrates that they have an optimal grade for execution. It is concluded that before applying the proposal the students were at low levels of coordination, however after its application there was an improvement in these aspects, thus demonstrating the effectiveness of the pedagogical proposal of recreational games for the development of coordination. Keywords: motor coordination, recreational games, 3JS test, methods, strategies, recreation.